2022
DOI: 10.3389/fnut.2022.927434
|View full text |Cite
|
Sign up to set email alerts
|

Valerian essential oil for treating insomnia via the serotonergic synapse pathway

Abstract: Valerian volatile oil can be used in the treatment of insomnia; however, the active components and mechanisms of action are currently unclear. Therefore, we used transcriptome sequencing and weight coefficient network pharmacology to predict the effective components and mechanism of action of valerian volatile oil in an insomnia model induced by intraperitoneal injection of para-Chlorophenylalanine (PCPA) in SD rats. Valerian essential oil was given orally for treatment and the contents of 5-hydroxytryptamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Its serum level is associated with anxiolytic and antidepressant effects of agarwood, possibly via multiple neuroactive pathways, including serotonergic synapse and neuroactive ligand–receptor interaction [ 56 ]. Wang et al also found that β-caryophyllene (one out of sixty-two sesquiterpenoids in agarwood) might activate the serotonergic synapse signaling pathway to increase the activity or affinity of the 5-HT, thus alleviating anxiety [ 57 ]. In another study on the anxiolytic and antidepressant effects, a mixture of rosifoliol and agaraspirol with different doses was reported to have some influence on the 5-HT 1A receptor in the serotonergic system [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its serum level is associated with anxiolytic and antidepressant effects of agarwood, possibly via multiple neuroactive pathways, including serotonergic synapse and neuroactive ligand–receptor interaction [ 56 ]. Wang et al also found that β-caryophyllene (one out of sixty-two sesquiterpenoids in agarwood) might activate the serotonergic synapse signaling pathway to increase the activity or affinity of the 5-HT, thus alleviating anxiety [ 57 ]. In another study on the anxiolytic and antidepressant effects, a mixture of rosifoliol and agaraspirol with different doses was reported to have some influence on the 5-HT 1A receptor in the serotonergic system [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with the signaling pathway of HIF-1 and ferroptosis, serotonergic synapse-related DEGs were usually significantly enriched ( 17 ). The serotonergic synapse signal pathway was activated by the core gene protein kinase PKA and the expression of 5-HT and GABA was increased, hence insomnia symptoms were improved and anxiety was alleviated ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…After aromatherapy using lavender oil, 24-h urine-free-cortisol level was reduced. A previous study reported a significant decrease in cortisol levels in saliva and sleep induction after a bath with lavender oil in pregnant women and young infants ( Field et al ., 2008 ; Wang et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%